Peningkatan Hasil Belajar Lempar Turbo Melalui Permainan Supir (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this research is to improve learning outcomes turbo throw at Elementary School fifth grade students Onions 02 through an application of game modifications driver. This study uses a classroom action research. The design of classroom action research was conducted in two cycles with the stages of planning, action, observation, and reflection. The subjects were students of class V Elementary School Onions 02 Onions District of Batang. Data collection techniques using the test method, the method of documentation, and the first cycle angket. Pada completeness of student learning outcomes increases with the number of students who achieve passing grade of 24 students, 17 students who scored> 75, with learning completeness 71% and in the second cycle number students who achieve mastery learning increased to 88% 21 students who scored> 75, when viewed from mastery learning in the first cycle and the second cycle only 3 students who do not achieve mastery study. Simpulan of this research is learning through play driver can improve results learn to throw turbo Elementary School fifth grade students of the District 02 Onion Onion, Batang year 2013/2014 lesson.